Digital Servant Leadership and Public Innovation: The Mediating Role of Cultural Values in Indonesian State Owned Enterprises - Nursaid; Qomariah, Nurul; Utomo, Bekti; Wahidah, Nurul Jannatul; Wisudawati, Tri (Novatio : Journal of Management Technology and Innovation, 2025)
This study examines how digital servant leadership (DSL) influences hackathon innovation performance in Indonesian State-Owned Enterprises (SOEs), with a focus on the mediating role of AKHLAK cultural values. Amidst ongoing digital transformation, SOEs have embraced DSL as a leadership style that emphasizes inclusivity, empowerment, and ethical service delivery. The study utilizes a mixed method approach comprising descriptive statistics and Structural Equation Modeling using Partial Least Squares (PLS SEM) to analyze quantitative and qualitative data gathered between November 2023 and January 2024. Key findings reveal that DSL significantly enhances innovation outcomes by fostering a psychologically safe, collaborative environment essential for successful hackathon execution. The presence of AKHLAK values Amanah, Kompeten, Harmonis, Loyal, Adaptif, and Kolaboratif strengthens cultural alignment, acting as a mediator that links leadership behaviors to employee engagement and innovation performance. Hackathons hosted by SOEs demonstrate varied formats, scales, and domains, yet all share critical success factors such as structured mentorship, inclusive participation, and strong post event support systems. The analysis of measurement and structural models shows robust construct validity and reliability across all latent variables. Convergent and discriminant validity meet accepted thresholds, while predictive relevance and model fit indices confirm the soundness of the proposed framework. Statistical mediation effects highlight the transformative impact of AKHLAK in linking DSL to performance gains in public service innovation. These findings contribute to public sector leadership theory and practice by proposing a replicable framework that combines digital servant leadership, AKHLAK-based cultural alignment, and participatory innovation formats. The Indonesian experience offers insights for other developing nations seeking to embed ethical leadership into digital transformation agendas. By institutionalizing values and enabling employee driven innovation, SOEs can better navigate complex governance landscapes while delivering measurable public value.